2006
DOI: 10.1196/annals.1317.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of VIP on TLR2 and TLR4 Expression in Lymph Node Immune Cells During TNBS‐Induced Colitis

Abstract: Toll-like receptors (TLRs) are a family of pattern recognition receptors (PRRs), which recognize numerous molecules collectively named pathogen-associated molecular patterns, with an essential role in inflammatory conditions and connecting innate and acquired immune responses. Moreover, a new function of TLRs in the intestinal mucosa has been described. Under homeostatic conditions, TLRs act to protect the intestinal epithelium; but when homeostasis is disrupted, TLRs appear deregulated. Disruption of intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 13 publications
(13 reference statements)
0
22
0
Order By: Relevance
“…Some studies, [254,255,256], have reported that administration of VIP ameliorated the trinitrobenzensulfonic acid (TNBS)-induced experimental colitis, a murine model of human CD associated with down-regulation of Th1-driven autoimmune responses and modifying IL-1, IL-6, TNF-and IFN-expression as well as increasing the antiinflammatory IL-10 and the Th2 cytokine IL-4. The same authors amplify the antiinflammatory mechanism of VIP by reducing TLR-2 and TLR-4 expression on macrophages, T cells, and DCs [257]. Newman et al [258] have found divergent data where, in a comparable animal model of intestinal inflammation, VIP was unable to ameliorate the clinical and histopathological markers of disease and to modify/regulate the Th1/Th2 cytokine profile in TNBS-challenged mice.…”
Section: In Vitro and Experimental Ibd Studiesmentioning
confidence: 94%
“…Some studies, [254,255,256], have reported that administration of VIP ameliorated the trinitrobenzensulfonic acid (TNBS)-induced experimental colitis, a murine model of human CD associated with down-regulation of Th1-driven autoimmune responses and modifying IL-1, IL-6, TNF-and IFN-expression as well as increasing the antiinflammatory IL-10 and the Th2 cytokine IL-4. The same authors amplify the antiinflammatory mechanism of VIP by reducing TLR-2 and TLR-4 expression on macrophages, T cells, and DCs [257]. Newman et al [258] have found divergent data where, in a comparable animal model of intestinal inflammation, VIP was unable to ameliorate the clinical and histopathological markers of disease and to modify/regulate the Th1/Th2 cytokine profile in TNBS-challenged mice.…”
Section: In Vitro and Experimental Ibd Studiesmentioning
confidence: 94%
“…Indeed, in MLN there was a significant decrease in absolute cell numbers on day 3 and a more drastic one on day 5 after the induction of the disease. Regarding the different cell populations present in MLN, the proportion of M⌽ (CD11b+) and DCs (CD11c+) was increased on days 5 and 7, whereas there was a significant reduction of lymphocytes at these time points [9,10] . Interestingly, the percentage of T CD4+ cells on days 5 and 7 and T CD8+ cells on day 5 was reduced, but TNBS triggered a significant increase in B CD19+ cell number on day 5 ( table 1 ).…”
Section: Cellular Traffic From/to Mesenteric Lymph Nodes: Apcs and T mentioning
confidence: 95%
“…1 ). Treatment with 1 nmol of VIP every other day resulted in an inhibition of this overexpression of TLR2 and TLR4, both approaching steady-state levels [9,10] . Moreover, VIP-induced modulation of TLR expression has been corroborated in human monocytic THP1 cells and peripheral blood monocytes [26] as well as in fibroblast-like synoviocytes from patients with rheumatoid arthritis [27,28] .…”
Section: Validation Of the Therapeutic Utility Through Its Tlr Modulamentioning
confidence: 99%
“…Treatment with VIP decreased the levels of a wide array of chemokines and proinflammatory cytokines [14]. In addition, VIP downregulated the expression of toll-like receptors (TLR)-2 and 4 in the colon and mesenteric lymph nodes of TNBS-treated animals [15,16]. These latter receptors have been depicted as innate immune sensors of bacterial and other pathogen components and have been implicated in inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%